Amplified prevalence and incidence of cardiovascular disease in patients with inflammatory arthritis and coexistent autoimmune disorders. (18th January 2020) - Heslinga, Maaike; Nielen, Mark M J; Smulders, Yvo; Simsek, Suat; Nurmohamed, Mike T
Abstract: Objective: This study aims to assess the prevalence proportion and incidence rate of cardiovascular morbidity in patients with inflammatory arthritis compared with that in controls, and to determine whether the co-existence of multiple autoimmune disorders is associated with an amplified risk of cardiovascular disease. Methods: Data from the Nivel Primary Care Database were used to assess prevalence proportion and incidence rate of cardiovascular disease in patients with inflammatory arthritis only, patients with inflammatory arthritis coexistent with another autoimmune disorder, and controls. Hazard ratios were calculated using Cox regression models. Results: The prevalence proportions in inflammatory arthritis patients were increased for type 1 diabetes [odds ratio (OR) 1.80, 95% CI: 1.27, 2.55], hypothyroidism (OR 1.49, 95% CI: 1.37, 1.61), psoriasis (OR 2.72, 95% CI: 2.49, 2.97) and IBD (OR 2.64, 95% CI: 2.28, 3.07) compared with that in controls. Cardiovascular disease prevalence (OR 1.34, 95% CI: 1.28, 1.41) and incidence rates (incidence rate ratio 1.3, 95% CI: 1.23, 1.41) were higher in inflammatory arthritis patients compared with that in controls, and were further increased in the presence of a second autoimmune disorder. The hazard ratio for cardiovascular disease was 1.32 (95% CI: 1.23, 1.41) for patients with inflammatory arthritis only, and 1.49 (95% CI: 1.31, 1.68) for patients with inflammatory arthritis co-existent with another autoimmune disorder. Conclusion: The amplification of cardiovascular disease risk in inflammatory arthritis patients with multiple autoimmune disorders warrants greater awareness, and since autoimmune disorders often co-exist, the need for cardiovascular risk management in these patients is once again emphasized.